UISU Siantar Private High School Strategic Management Based on Internal Environmental Analysis - Puri*, Dian Ratna; Siregar, Yeni Saufina; Khairani, Yeni; Daryanto, Eka; Rosnelli, Rosnelli (Riwayat: Educational Journal of History and Humanities, 2023)
Strategic management is planning, monitoring, analysis and evaluation that is carried out on an ongoing basis from all the needs needed by organizations both in the world of education in an effort to achieve their goals. The purpose of strategic management in the world of education is an effort to improve education based on established laws. The implementation of strategic management of the school environment includes internal and external analysis and reaches a strategic evaluation to determine the extent to which results have been achieved. This study aims to describe the strategic management of Uisu Siantar Private High School based on an analysis of the internal environment. The internal environment is an environment that has a direct influence on the operation of educational institutions, such as curriculum, students, teaching and educational staff, facilities and infrastructure as the potential of the school itself, the competitive situation, the situation of educational customers, and graduate users. Everything influences the determination of strategies that are expected to support the school in achieving its goals. This study uses a qualitative approach and descriptive type. While collecting data using interviews, observation, and documentation. Data analysis techniques use data presentation and conclusion. The application of strategic management in education is carried out through the preparation of strategy formulation and strategy implementation, by combining school-based management.